Annual World Bank Conference on Development Economics, 2001/2002 (Washington, D.C. World Bank, 2002)
"The 13th annual conference, held in May 2001, concentrated on the current thinking in development policy and the implications for the global economy with a particular focus on the two important and controversial themes of globalization and health."
Includes bibliographical references.
Keywords: Economics; Developing countries -- Economic conditions -- Congresses; Developing countries -- Economic policy -- Congresses; Electronic books